2005
DOI: 10.1007/s00248-004-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of Wild Bird Feathers Revealed throughCulture-Based and Culture-Independent Techniques

Abstract: Despite recent interest in the interactions between birds and environmental microbes, the identities of the bacteria that inhabit the feathers of wild birds remain largely unknown. We used culture-based and culture-independent surveys of the feathers of eastern bluebirds (Sialis sialis) to examine bacterial flora. When used to analyze feathers taken from the same birds, the two survey techniques produced different results. Species of the poorly defined genus Pseudomonas were most common in the molecular survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 38 publications
4
71
0
Order By: Relevance
“…In all cases, the DNA sequencing analysis matched the original FAME identification, suggesting that the latter was a suitable and reliable identification method for the isolates in this study, as previously found for bird feather microbiota [51].…”
Section: Microbial Identificationsupporting
confidence: 81%
See 4 more Smart Citations
“…In all cases, the DNA sequencing analysis matched the original FAME identification, suggesting that the latter was a suitable and reliable identification method for the isolates in this study, as previously found for bird feather microbiota [51].…”
Section: Microbial Identificationsupporting
confidence: 81%
“…dominated the nest samples, since Bacillus spp. has been found to dominate feather samples using similar culture techniques to those used here [51].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations